More Questions Than Answers: A Response to Stephens, Reeder, And Elder - Robert D. Bhaerman (Journal of Research in Rural Education, 1992)
In responding to the papers by Stevens, Reeder, and Elder, I have organized my comments along the following questions: What is a policy-impact code? What are the problems that a code would address, and how would it address them? How does one construct such a code? What are the benefits and uses of a code? As my comments indicate, I believe there are more questions than answers in the complex field of designing policy-impact codes.